Correction: A facile hard-templating synthesis of mesoporous spinel CoFe2O4 nanostructures as promising electrocatalysts for the H2O2 reduction reaction. Issue 48 (28th May 2015) - Ding, Rui; Lv, LeiLei; Qi, Li; Jia, Mingjun; Wang, Hongyu
<x xml:space="preserve">Abstract</x> Correction for 'A facile hard-templating synthesis of mesoporous spinel CoFe2O4 nanostructures as promising electrocatalysts for the H2O2 reduction reaction' by Rui Ding et al., RSC Adv., 2014, 4, 1754–1760.